Explicitation and Implicitation through Translation Shifts in the Annual Reports from Indonesian to English - Octoveria, Emma Natasha; Munandar, Aris (Soegijapranata Catholic University, 2023)
Language serves a significant role in many forms of international business communication, one of which is the translation of annual reports. The primary objective of this study is to investigate the manner in which translation shifts can uncover explicitations and implicitations in the process of translating annual reports from Indonesian to English. Additionally, it seeks to identify aspects of translation that are made more explicit and implicit through translation shifts. This study incorporates Catford’s (1965) and Becher’s (2011) classifications of translation shifts to reveal the forms and functions of translation shifts for the purposes of explicitation and implicitation. We obtained the data from six annual reports of public companies in Indonesia. Through a descriptive-qualitative analysis, we discovered that the translation of annual reports from Indonesian to English performed explicitations through intra-system shifts and implicitations through structure-shifts. The study reveals how translation shifts do not only modify the syntactic structure of the target text, but they also modify the information load in the translation of annual reports from Indonesian to English.